Cabin Fever : the harrowing journey of a cruise ship at the dawn of a pandemic - Smith, Michael, (Journalist); Franklin, Jonathan, 1964- (New York : Doubleday, a division of Penguin Random House LLC, 2022)
"A harrowing narrative of the Holland America cruise ship Zaandam, which set sail with a deadly and little-understood stowaway-Covid-19-days before the world shut down in March, 2020. In early 2020, the world was on edge. An ominous virus was spreading on different continents, and no one knew what the coming weeks would bring. Far from the hotspots, the cruise ship Zaandam, owned by Holland America, was preparing to sail from Buenos Aires, Argentina, loaded with 1,200 passengers-Americans, Europeans and South Americans, plus 600 crew. Most passengers were over the age of 65. There was concern about the virus on the news, and it had already killed and sickened passengers on other Holland America ships. But that was oceans away, and escaping to sea at the ends of the earth for a few weeks seemed like it might be a good option. The cruise line had said the voyage (three weeks around the South American coastline to see some of the most world's most stunning natural wonders and ancient ruins) would carry on as scheduled, with no refunds. And it would be safe. Cabin Fever is a riveting narrative thriller, taking readers behind the scenes of the ship's complex workings, and below decks into the personal lives of passengers and crew who were caught unprepared for the deadly ordeal that lay ahead. There is a retired American school superintendent on a dream vacation with his wife of 56 years, on a personal quest to see Machu Picchu. There is an Argentine psychologist taking this trip to celebrate her 64th birthday with her husband, though she finds herself fretting in her cabin on Day One, trying to dismiss her fears of what she's hearing on the news. There is an Indonesian laundry manager who's been toiling on Holland America cruise ships for thirty years, sending his monthly paycheck to his family back home. Within days, people aboard Zaandam begin to fall sick. The world's ports shut down. Zaandam becomes a top story on the news and is denied safe harbor everywhere. With only two doctors aboard and few medical supplies to test for or treat Covid-19, and with dwindling food and water, the ship wanders the oceans on an unthinkable journey"--.
Choose fun! -- Mysterious stowaway -- Ugly vibe at the ends of the earth -- Cruise to nowhere -- Lockdown in the Pacific -- Secret mission -- Pariah ship -- Dark thoughts -- Night crossing -- Desperate plea -- Race to shore -- Trapped on dry land -- Prisoners in paradise -- Final goodbye -- Unfamiliar horizons.
new book 2022 fall.
Keywords: Zaandam (Cruise ship); COVID-19 (Disease); COVID-19 Pandemic, 2020-2023; Cruise ships; Travel -- Health aspects; Ships -- Disinfection